Spontaneous recovery from post‐COVID‐19 brain fog - Teruaki Hayashi; Masaaki Iwata (PCN Reports, 2024)
Abstract Background One‐third of individuals who contract novel coronavirus disease 2019 (COVID‐19) reportedly experience persistent symptoms, including respiratory issues, headache, dizziness, taste disorders, fatigue, and various psychiatric and neurological symptoms, known as post‐acute sequelae of SARS‐CoV‐2. In this case report, we present a patient who became aware of brain fog, which is cognitive impairment, approximately 2 months after their COVID‐19 symptoms had resolved, accompanied by anxiety and depression. Case Presentation The patient, a 35‐year‐old Japanese man, was infected with COVID‐19 and resumed work approximately 2 weeks later after symptoms improved. Approximately 1 month after returning to work, the patient's concentration became impaired and he started making noticeable errors at work. These symptoms did not improve, leading him to the outpatient clinic specializing in COVID‐19 sequelae at our hospital. Here, he underwent blood tests, electroencephalography, and head magnetic resonance imaging, which did not reveal any abnormalities. Cognitive decline due to COVID‐19 sequelae was therefore suspected, prompting his evaluation in our department approximately 5 months after his initial COVID‐19 infection. Detailed cognitive function tests were performed. He was monitored without the use of medications, and his cognitive function gradually improved. Approximately 11 months after his initial COVID‐19 infection, the same cognitive function tests were conducted again, because his subjective cognitive function symptoms had disappeared, and improvement was observed in many items. Conclusion Since brain fog is a relatively common sequela, we emphasize the importance of keeping this in mind from the initial consultations and comparing results over time.